2011
DOI: 10.1177/003335491112600311
|View full text |Cite
|
Sign up to set email alerts
|

Prospectively Assessed Posttraumatic Stress Disorder and Associated Physical Activity

Abstract: Objectives. We examined the association of physical activity with prospectively assessed posttraumatic stress disorder (PTSD) symptoms in a military cohort.Methods. Using baseline and follow-up questionnaire data from a large prospective study of U.S. service members, we applied multivariable logistic regression to examine the adjusted odds of new-onset and persistent PTSD symptoms associated with light/moderate physical activity, vigorous physical activity, and strength training at follow-up. Conclusions. Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 52 publications
2
45
1
6
Order By: Relevance
“…For instance, the early parental loss is a protective factor for panic (OR = 0.9, 95% CI = 0.7–1.0), but a risk factor for PTSD (OR = 1.2, 95% CI = 1.0–1.4) (Blanco et al, ). Although we have found effects only for PTSD and agoraphobia, due to the small number of studies included in subgroup analysis, only two studies provided data for incident agoraphobia (Strohle et al, ; Ten Have et al, ), PTSD (LeardMann et al, ; Strohle et al, ), panic Strohle et al, ; Ten Have et al, ), OCD (Strohle et al, ; Ten Have et al, ), social phobia (Strohle et al, ; Ten Have et al, ), and specific phobias (Strohle et al, ; Ten Have et al, ), and four for GAD (McDowell, Dishman et al, ; Strohle et al, ; Ten Have et al, ; Zainal & Newman, ), it is precocious to determine whether these effects are common to all anxiety disorders or are disorder‐specific and more research is needed to adequately address this point.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, the early parental loss is a protective factor for panic (OR = 0.9, 95% CI = 0.7–1.0), but a risk factor for PTSD (OR = 1.2, 95% CI = 1.0–1.4) (Blanco et al, ). Although we have found effects only for PTSD and agoraphobia, due to the small number of studies included in subgroup analysis, only two studies provided data for incident agoraphobia (Strohle et al, ; Ten Have et al, ), PTSD (LeardMann et al, ; Strohle et al, ), panic Strohle et al, ; Ten Have et al, ), OCD (Strohle et al, ; Ten Have et al, ), social phobia (Strohle et al, ; Ten Have et al, ), and specific phobias (Strohle et al, ; Ten Have et al, ), and four for GAD (McDowell, Dishman et al, ; Strohle et al, ; Ten Have et al, ; Zainal & Newman, ), it is precocious to determine whether these effects are common to all anxiety disorders or are disorder‐specific and more research is needed to adequately address this point.…”
Section: Discussionmentioning
confidence: 81%
“…From a measurement perspective, assessments of stress and PA are often mismatched, with one measure inquiring about stress over a given period (e.g., the last month; Perceived Stress Scale [PSS]) and the other inquiring about PA over a different period of time (e.g., the last year, Modifiable Activity Questionnaire [MAQ]) [124, 191, 259, 286, 295]. Prospective studies, while an improvement over cross-sectional ones, do not always gauge stress and PA at each time point [268, 279]. This is important to determine bi-directional associations of stress and PA. Diary studies have provided considerable improvement in this respect, while also being less affected by stress-related memory deficits [17, 189].…”
Section: Discussionmentioning
confidence: 99%
“…Those who drop out of studies tend to have higher stress and anxiety, which could also mask any potential effects [188]. Several studies finding an inverse trend of a stress–PA association have been underpowered [277], while others are overpowered, detecting trivial associations [260, 268, 270, 272, 316]. Studies with large samples of inactive participants (or conversely all active subjects) may not have enough variability in exercise measures to detect an effect [273].…”
Section: Discussionmentioning
confidence: 99%
“…Study by Leard Mann et al, showed that by increasing physical activity, the level of stress decreases. 34 This could be due to the fact that physical activity and exercise makes the mother feel fresh and lively, and it releases endorphins in the body that is very effective in reducing stress. In this study significant reverse relationship were observed between perceived stresses and responsibility for health.…”
Section: Discussionmentioning
confidence: 99%